The transatlantic security dilemma after 9/11: Lessons from Britain – the role of Tony Blair - Balla, Evanthia (2015)
The current study analyses the transatlantic security environment after 9/11 –transatlantic strategic cultures, ESDP developments, ESDP- NATO relations and Blair’s political answer as a European leader. It seeks to draw some specific lessons over the best way the transatlantic community and especially Europe shall meet the global challenges of our times.